Perancangan dan Analisis Ekonomi Pembangunan Pembangkit Listrik Tenaga Piko Hidro di Desa Garabak Data Kabupaten Solok Sumatera Barat - Adly Havendri; Dendi Adi Saputra; Mulya Cipta Nurmansyah (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
In this research, development of a pico hydro power plant utilizing the river with water flow 0.6 m3/s and head 1.5 m is conducted. According to the available potential of the area, the waterwheel turbine with type undershot and efficiency about 71-76% is selected. The synchronize generator with 1 phase and 10 kVA capacity is chosen according the maximum generated power of the plant power which is about 8.81 kW. Due to the loses inside the turbine and generator, therefore the average electrical power that can be distributed is 4.96 kW. For stabilizing the voltage and current from the generator, a 7,5 kVA stabilizer with safety factor 20% is used. As the result, the stable electrical power 34.759,68 kWh can be generated every year with the capacity factor about 80%. The design results of the pico hydro power plant indicated that the power plant in Garabak Data able to produce the electrical power about Rp899,05 per kWh.